Security issues and quality of service in real time wireless PLC/SCADA process control systems - Eren, Halit; Hatipoglu, D. (Institute of Electrical and Electronics Engineers (IEEE), Piscataway, NJ, USA, 2008)
Abstract: A wireless PLC/SCADA network has been set up to investigate the reliability of wireless communication systems in a local area network. It has been shown that the integrity of data flow can be maintained within certain limits of the signal strength in a coverage area of an Access Point. The Wi-Fi can successfully be applied in industrial operations provided a careful site surveys has been be conducted and the boundaries are determined to ensure adequate signal strength to avoid any possible dropouts however short lived they may be. It has also been shown that if the dropout occurs the self repair capability of the communication system may not be sufficient thus requiring manual interference that may not be tolerable in many process control operations. (15 refs.)